2020
DOI: 10.48550/arxiv.2002.00389
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Resonant amplified seismic response within a hill or mountain

Armand Wirgin

Abstract: We show theoretically what is meant by the term '(surface shape) resonance' in connection with the seismic response of a protuberance (emerging from flat ground) such as a hill or mountain of arbitrary shape. We address the specific problem of cylindrical protuberances of rectangular shape submitted to a SH plane wave. We find that the principal (i.e., qualitative) characteristics of the seismic response of a mountain are quite similar to those of a hill, and that the occurrence of significative amplification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 212 publications
(410 reference statements)
0
16
0
Order By: Relevance
“…Our parametric study is justified by the fact that a protuberance (e.g., dike, hill or mountain) gives rise to a large variety of seismic responses and that it has not, until now, been possible to identify the principal features of the incident wave, the protuberance, and the underground (to which the protuberance is connected), that condition these responses. In [29] we showed why these, often amplified, responses are largely the result of the coupling of the incident wave to (surface shape) resonances, but, we still do not know how these resonances (i.e., their frequencies of occurrence and amplitudes) depend on the various parameters of the wave-structure interaction.…”
Section: The Contours Of the Parametric Studymentioning
confidence: 95%
See 4 more Smart Citations
“…Our parametric study is justified by the fact that a protuberance (e.g., dike, hill or mountain) gives rise to a large variety of seismic responses and that it has not, until now, been possible to identify the principal features of the incident wave, the protuberance, and the underground (to which the protuberance is connected), that condition these responses. In [29] we showed why these, often amplified, responses are largely the result of the coupling of the incident wave to (surface shape) resonances, but, we still do not know how these resonances (i.e., their frequencies of occurrence and amplitudes) depend on the various parameters of the wave-structure interaction.…”
Section: The Contours Of the Parametric Studymentioning
confidence: 95%
“…Moreover, our previous contribution [29] showed that the seismic response of each configuration, at a given frequency, tends to be spatially non-uniform, so that this is the cause of another computational difficulty (i.e., the determination of the field at a great number of points in a domain that includes the protuberance and a portion of the underground). But, all in all, these voluminous computations are not out of reach of what modern digital computers can do in a reasonable length of time.…”
Section: The Contours Of the Parametric Studymentioning
confidence: 99%
See 3 more Smart Citations